2015
DOI: 10.1103/physreva.91.062121
|View full text |Cite
|
Sign up to set email alerts
|

Waveguide-QED-based measurement of a reservoir spectral density

Abstract: The spectral density (SD) function has a central role in the study of open quantum systems (OQSs). We discover a method allowing for a "static" measurement of the SD -i.e., it requires neither the OQS to be initially excited nor its time evolution tracked in time -which is not limited to the weak-coupling regime. This is achieved through one-dimensional photon scattering for a zero-temperature reservoir coupled to a two-level OQS via the rotating wave approximation. We find that the SD profile is a universal s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…A quantum emitter coupled to a homogeneous photonic reservoir has interesting analogies with the textbook impurity problem in condensed matter [16]. For instance, the reflection and transmission coefficients of a photon scattering off an atom in a waveguide are formally the same as those for an impurity described by an effective, energy-dependent, scattering potential [17,18]. Moreover, as first suggested in Ref.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation

Dressed emitters as impurities

Leonforte,
Valenti,
Spagnolo
et al. 2021
Preprint
Self Cite
“…A quantum emitter coupled to a homogeneous photonic reservoir has interesting analogies with the textbook impurity problem in condensed matter [16]. For instance, the reflection and transmission coefficients of a photon scattering off an atom in a waveguide are formally the same as those for an impurity described by an effective, energy-dependent, scattering potential [17,18]. Moreover, as first suggested in Ref.…”
Section: Introductionmentioning
confidence: 86%
“…Notice that, for z / ∈ R, generally F 12 = F * 21 , and that |Ψ i (z) and F ii (z) coincide with Eqs. ( 17) and (18), respectively, when |0 is replaced by |x i .…”
Section: More Than One Emittermentioning
confidence: 99%

Dressed emitters as impurities

Leonforte,
Valenti,
Spagnolo
et al. 2021
Preprint
Self Cite
“…In figure 2(b), we plot the maximal ratio xm x0 c w c ( )/ of the susceptibility with a different environment as a function of the equivalent damping rate eff g . Here, eff g is a spectrum-dependent parameter which describes the dissipation strength of the structured bath; through the inverse Laplace transform of w S( ), we have eff m  g p w » ( ) [38]. Under this condition, eff g is proportional to the system-bath coupling strength η.…”
Section: Mechanical Susceptibility and Thermal Correlation With A Strmentioning
confidence: 99%
“…Theoretically, the waveguide can be treated as structured reservoirs [35][36][37][38][39], and the theory of non-Markovian quantum open system is an effective method to study the dynamics of the objects coupling to the reservoir. In cavity quantum electrodynamics regime, the structured reservoir can be photonic crystals or waveguides [37,[40][41][42][43][44]. It has been shown that the bound states without dissipation can be formed when system coupled to band gaps or finite band spectrum [36,45] which is easily satisfied in photonic crystals or waveguides [35,36,41,46,47].…”
Section: Introductionmentioning
confidence: 99%